The Discrete Self-Adjoint Dirac Systems of General Type: Explicit Solutions of Direct and Inverse Problems, Asymptotics of Verblunsky-Type Coefficients and the Stability of Solving of the Inverse Problem - Roitberg, I.; Sakhnovich, A. (Журнал математической физики, анализа, геометрии, 2018)
We consider discrete self-adjoint Dirac systems determined by the potentials (sequences) Ck such that the matrices Ck are positive definite and j-unitary, where j is a diagonal m × m matrix which has m1 entries 1 and m2 entries –1 (m1 +m2 = m) on the main diagonal. We construct systems with the rational Weyl functions and explicitly solve the inverse problem to recover systems from the contractive rational Weyl functions. Moreover, we study the stability of this procedure. The matrices Ck (in the potentials) are the so-called Halmos extensions of the Verblunsky-type coefficients ρk. We show that in the case of the contractive rational Weyl functions the coefficients ρk tend to zero and the matrices Ck tend to the identity matrix Im. Розглянуто дискретнi самоспряженi системи Дiрака, визначенi потенцiалами (послiдовностями) Ck так, що матрицi Ck є позитивновизначеними та j-унiтарними, де j = це дiагональна матриця розмiру m × m, що має на головнiй дiагоналi m1 та m2 елементiв, якi дорiвнюють вiдповiдно 1 та 1 (m1 + m2 = m). У роботi побудовано системи з рацiональними функцiями Вейля та точно розв’язано обернену задачу вiдновлення системи за стискальними рацiональними функцiями Вейля. Крiм цього, у роботi дослiджується стiйкiсть цiєї процедури. Матрицi Ck (з потенцiалiв) = це так званi розширення Халмоша коефiцiєнтiв ρk типу Верблюнського. У роботi доведено, що у випадку стискальної рацiональної функцiї Вейля коефiцiєнти ρk прямують до нуля, а матрицi Ck прямують до одиничної матрицi Im.